Automated Multi-Dataset Analysis (AMDA): An on-line database and analysis tool for heliospheric and planetary plasma data. (July 2021) - Génot, V.; Budnik, E.; Jacquey, C.; Bouchemit, M.; Renard, B.; Dufourg, N.; André, N.; Cecconi, B.; Pitout, F.; Lavraud, B.; Fedorov, A.; Ganfloff, M.; et al.
Abstract: Accessing, visualizing and analyzing heterogeneous plasma datasets has always been a tedious task that hindered students and senior researchers as well. Offering user friendly and versatile tools to perform basic research tasks is therefore pivotal for data centres including the Centre de Données de la Physique des Plasmas (CDPP http://www.cdpp.eu/ ) which holds a large variety of plasma data from various Earth, planetary and heliophysics missions and observatories in plasma physics. This clearly helps gaining increased attention, relevant feedback, and enhanced science return on data. These are the key ideas that crystallized at CDPP more than 15 years ago and resulted in the lay-out of the concepts, and then development, of AMDA, the Automated Multi-Dataset Analysis software (http://amda.cdpp.eu/ ). This paper gives a description of the architecture of AMDA, describes its functionalities, presents some use cases taken from the literature or fruitful collaborations and shows how it offers unique capabilities for educational purposes. Graphical abstract: Image 1 Highlights: AMDA (Automated Multi-Dataset Analysis) is an online analysis software and database of in-situ and modeled plasma data in heliophysics and planetary sciences. AMDA is used in support to science exploitation for a large variety of missions. AMDA is used by hundreds of students and researchers and facilitated the publication of tens of papers.